Myelodysplastic syndromes: histopathology as prognostic factor - Romeo,Maura (2001)
Bone marrow biopsy allows evaluation of cellularity, abnormal localization of immature precursors and fibrosis in myelodysplastic syndrome. It has been considered important to make diagnosis and prognosis of this disorder. The object of this study evaluated the influence of histopathological parameters, such as cellularity, erythroid/myeloid ratio, abnormal localization of immature precursors and marrow fibrosis, on survival of myelodysplastic syndrome patients. Forty-six patients, admitted from April 1985 to June 1998, and diagnosed as being myelodysplastic syndrome according to French-American-British criteria, were selected. There were 20 males and 26 females, with median age of 61 years. Forty-six bone marrow smears and 36 trephine biopsies were reviewed. Mean survival of hypocellular cases was 64.8 months and of hyper and normocellular cases was 31.8 months. Patients with predominance of erythroid hyperplasia had mean survival of 50.8 months, greater than those with predominance of myeloid hyperplasia (20.3 months). There was no statistical difference in survival of patients with or without abnormal localization of immature precursors and with or without marrow fibrosis. Bone marrow biopsy is a useful tool for the identification of parameters that influence prognosis in myelodysplastic syndrome. Hypocellularity and erythroid hyperplasia were correlated with longer survival while myeloid hyperplasia with poorer survival.